Pengaruh Layanan Berbasis Protokol Kesehatan Terhadap Kepuasan Konsumen Pada Pengguna Jasa Transportasi Grabcar Oleh Mahasiswa Universitas Atma Jaya Makassar - Prisilia Yosafat, Widya; Lallo Pakiding, Daniel; Lusdani, Westerini (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2022)
The purpose of this study is to analyze and examine the effect of health protocol-based services Tangible, Reliability, Responsiveness, Assurance, and Empathy for consumer satisfaction GrabCar transportation service during the covid-19 pandemic.This reseacrh uses associative method. Collecting data using a questionnaire distributed to the sample. The sample in this study amounted to 100 respondents who were students at the Atma Jaya Makassar University in the category of having used GrabCar based on health protocols or GrabCar Protect at least once. Data collection techniques using non-probability methods, the purposive sampling technique. The results of this study F test, show that the health protocol-based service variables consisting of Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy have a simultaneous effect on consumer satisfaction using GrabCar transportation services by Atma Jaya University Makassar students.